1999
DOI: 10.1046/j.1365-2672.1999.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation extract effects on the morphology and metabolism of the rumen fungus Neocallimastix frontalis EB188

Abstract: . 1999. The effects of Aspergillus oryzae fermentation extract, Amaferm TM , on the rumen fungus Neocallimastix frontalis EB188 were studied. The secretion of cellulase was increased by 67% and rhyzoid development was increased 3·8-fold in the presence of extract. Strength of fungal response increased in a dose-dependent manner and demonstrated a positive correlation between cell surface area and enzyme secretion. Above certain concentrations of extract, however, the development of the fungus and enzyme secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…To our knowledge, this study is the first to show an in vivo increase in ruminal F. succinogees and R. flavefaciens following AOC supplementation. The effects of AOC on stimulating rumen fermentation were consistent with the results of previous studies (Beharka & Nagaraja ; Chang et al ). The improvement of CMCase and amylase may be the result of increase of fungi, F. succinogees and R. flavefaciens .…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this study is the first to show an in vivo increase in ruminal F. succinogees and R. flavefaciens following AOC supplementation. The effects of AOC on stimulating rumen fermentation were consistent with the results of previous studies (Beharka & Nagaraja ; Chang et al ). The improvement of CMCase and amylase may be the result of increase of fungi, F. succinogees and R. flavefaciens .…”
Section: Discussionsupporting
confidence: 91%
“…Rumen fungi have a strong fibrolytic activity that helps in degradation of low quality roughages by breaking the linkages between lignin and hemicelluloses (Akin et al, 1983;Borneman et al, 1992;Paul et al, 2003). However, the fibre degradation can be affected, as the fungal enzymes are inhibited by the addition of certain microbial inhibitory compounds within the plant structure (Chang and Calza, 2002). Gordon and Phillips (1993) reported that sheep with fungi present in the rumen ate more of a straw based diet because of increased digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in total bacterial numbers is often accompanied by an increase in numbers of cellulolytic bacteria and VFA concentrations in the rumen (Newbold et al, 1992). Protozoal numbers apparently are not affected in the presence of Amaferm, but there are reports of positive effects of the additive on numbers and activity of the rumen fungi (Harper et al, 1996;Chang et al, 1999). It is thought that the increased cell wall degrading activity associated with increased bacterial and fungal numbers accounts, in part at least, for the often observed increase in fibre degradation in the rumen.…”
Section: Proposed Mode Of Action and Conditions Of Usementioning
confidence: 99%